(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2017)
Motivation factors play an important role in influencing learning. Motivation plays a very important role in human efforts to achieve the desired goals, in the field of education and other purposes. Motivation is impetus, it means there is a conscious effort to influence one’s behavior to move his heart to act to do something to achieve certain results or goals Purwanto (1996: 71). With the motivation learners can develop activities and initiatives that is able to direct and maintain persistence in learning activities. There are several forms and ways to foster motivation in school activities such as gift giving, score, praise, punishment, competition, repetition, and interest.